2015
DOI: 10.3390/rs70709410
|View full text |Cite
|
Sign up to set email alerts
|

Potential of C and X Band SAR for Shrub Growth Monitoring in Sub-Arctic Environments

Abstract: The Arctic and sub-Arctic environments have seen a rapid growth of shrub vegetation at the expense of the Arctic tundra in recent decades. In order to develop better tools to assess and understand this phenomenon, the sensitivity of multi-polarized SAR backscattering at C and X band to shrub density and height is studied under various conditions. RADARSAT-2 and TerraSAR-X images were acquired from November 2011 to March 2012 over the Umiujaq community in northern Quebec (56.55 • N, 76.55and compared to in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 40 publications
(32 reference statements)
3
40
0
Order By: Relevance
“…Fresh vegetation canopy can increase the fraction of volume scattering and positively affect backscatter intensity [27]. Existing studies on the effect of tundra vegetation on backscatter [23,32,56] do not address the effect of fresh vegetation on previously degraded tundra surfaces. The mixed signals of vegetated and eroding surfaces within the cliff AOIs could explain the higher standard deviations of backscatter in 2015.…”
Section: Backscatter Dynamics Of Tundra and Cliff Surfacesmentioning
confidence: 99%
“…Fresh vegetation canopy can increase the fraction of volume scattering and positively affect backscatter intensity [27]. Existing studies on the effect of tundra vegetation on backscatter [23,32,56] do not address the effect of fresh vegetation on previously degraded tundra surfaces. The mixed signals of vegetated and eroding surfaces within the cliff AOIs could explain the higher standard deviations of backscatter in 2015.…”
Section: Backscatter Dynamics Of Tundra and Cliff Surfacesmentioning
confidence: 99%
“…The study area is a 60-km 2 region situated in the vicinity of the Inuit community of Umiujaq (56.55°N, 76.55°W) on the eastern shore of the Hudson Bay, Nunavik (Northern Quebec, QC, Canada; see Figure 1), it has been used in many studies and described in a prior paper by Duguay et al [26]. It is a discontinuous permafrost zone positioned at the northern tree line, forming a transition between the forest tundra to the south and the shrub tundra to the north.…”
Section: Study Areamentioning
confidence: 99%
“…Classes with shrub coverage tend to retain more snow, as demonstrated in [1,2,12], which causes ground temperatures to be warmer during the winter, enabling a better differentiation from classes with little or no shrub coverage. The volume scattering component from the vegetation is also affected by snow cover, as snow tends to attenuate the scattering from the vegetation due to the lower dielectric contrast between the shrub branches and the snow [26].…”
Section: Class Symbolmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to bare ground and water, previous research has also demonstrated the sensitivity of TSX (VV/HH polarized) data to the presence of Arctic shrubs and vegetation communities in summer [83], as well as in winter under a dry snow cover [84]. Under both conditions, backscatter is expected to increase with higher shrub density because the fraction of volume scattering increases with taller vegetation.…”
Section: Technical Considerations For Using Tsx For Wet Snow Detectionmentioning
confidence: 99%